Structural evolution and mechanism of multi-phase rift basins: A case study of the Panyu 4 Sag in the Zhu Ⅰ Depression, Pearl River Mouth Basin, South China Sea - Guo, Bowei; Yu, Fusheng; Li, Hui (Frontiers in Earth Science, 2023)
The study of changes in normal fault systems during different rift stages is important to understand the genesis and evolution of multi-phase rift basins, such as the Panyu 4 Sag in the Zhu Ⅰ Depression. Using 2D and 3D seismic data and analogue modelling, the Zhu Ⅰ Depression was characterized as a series of half‐grabens bounded by NE-NEE-trending normal faults, it was found to have undergone two phases of the extension during the Paleogene. The Zhu Ⅰ Depression exhibited four fault sets with different strikes, including NNE, NE-NEE, EW, and NWW. The main controlling faults were NE-trending and EW-trending with high activity rates during Rift Phase 1 and Rift Phase 2, respectively. The average azimuths of the dominant strikes for type Ⅰa, type Ⅰb, and type Ⅱ faults were 75°, 85°, and 90°, which revealed that the minimum principal stress (σ3) directions during the rift phases 1 and 2 of the Zhu Ⅰ Depression were SSE (~165°) and near-EW (~180°), respectively. Two phases of structural-sedimentary evolution, with different directions and analogue modelling results, illustrated that the Panyu 4 Sag was formed as a superimposed basin under multi-phase anisotropic extension. The structural evolution of the Panyu 4 Sag since the Paleogene was mainly controlled by the combined effects of the Pacific, Eurasian, and Indian plates. Since the orientation of subduction of the Pacific plate changed from NNW to NWW, the stress field shifted from NW-SE-trending tension to S-N-trending tension, causing the superimposition of late near-E-W-oriented structural pattern on the early NE-oriented structural pattern.